Imaging assessment of calcinosis in juvenile dermatomyositis: a narrative review - Belina Y. Yi; Jessica Perfetto; Evin Rothschild; Kelly Rouster-Stevens; Amanda Robinson; Kathryn Cook; Delaney D. Ding; Andrea Eagle Child; Ovgu Kul Cinar; Barbara Limbach; Charalampia Papadopoulou; Lesley Ann Saketkoo; et al. (Pediatric Rheumatology Online Journal)
Abstract Calcinosis is a severe manifestation of juvenile and adult idiopathic inflammatory myopathies, which can lead to pain, limited range of motion, disfigurement, and infection. It is more common in juvenile idiopathic inflammatory myopathies, especially in juvenile dermatomyositis (JDM). Calcinosis can be visible on cutaneous surfaces, although can also present in muscles and internal organs, making a thorough assessment difficult without imaging modalities. In this narrative review, we discuss different imaging modalities used in evaluating JDM-associated calcinosis including X-ray, computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound (US).